Voltammetric assay of albendazole in pharmaceutical dosage forms - de Oliveira, M. F.; Stradiotto, Nelson Ramos [UNESP] (Marcel Dekker Inc, 2001)
A simple, rapid inexpensive voltammetric method have been developed for the quantitative determination of albendazole (ABZ) as the pure assay, by direct dissolution of commercial tablets in HCl solutions. Studies with linear sweep (LSV), square-wave (SWV) and differential pulse voltammetry (DPV) were carried out ABZ in aqueous medium at a glassy carbon electrode. A well defined irreversible oxidation peak current was obtained at 1,00V vs. SCE. The method permits a precise quantitative determination of ABZ using the standard addition method. The detection limits for the three voltammetric techniques were found to be 3.0 x 10(-5) M (LSV), 6.2 x 10(-5) M (SWV) and 4.0 x 10(-5) M (DPV).
Keywords: albendazole; differential pulse; square wave; linear sweep